Visualization of the recurrent laryngeal nerve alone versus intraoperative nerve monitoring in primary thyroidectomy: a framework approach to a missing typology - Papagoras, Dimitris; Tzikos, Georgios; Douridas, Gerasimos; Arseniou, Polyvios; Panagiotou, Dimitrios; Kanara, Maria; Papavramidis, Theodosios (Frontiers in Surgery, 2023)
Introduction: Surgical studies evaluating a device or technology in comparison to an established surgical technique should accurately report all the important components of the surgical technique in order to reduce the risk of intervention bias. In the debate of visualization of the recurrent laryngeal nerve alone (VONA) versus intraoperative nerve monitoring (IONM) during thyroidectomy, surgical technique plays a key role in both strategies. Our aim was to investigate whether the surgical technique was considered as a risk of intervention bias by relevant meta-analyses and reviews and if steps of surgical intervention were described in their included studies. Methods: We searched PUBMED, CENTRAL -Cochrane library, PROSPERO and GOOGLE for reviews and meta-analyses focusing on the comparison of IONM to VONA in primary open thyroidectomy. Τhen, primary studies were extracted from their reference lists. We developed a typology for surgical technique applied in primary studies and a framework approach for the evaluation of this typology by the meta-analyses and reviews. Results: Twelve meta-analyses, one review (388,252 nerves at risk), and 84 primary studies (128,720 patients) were included. Five meta-analyses considered the absence of typology regarding the surgical technique as a source of intervention bias; 48 primary studies (57.14%) provided information about at least one item of the typology components and only 1 for all of them. Discussion: Surgical technique of thyroidectomy in terms of a typology is underreported in studies and undervalued by meta-analyses comparing VONA to IONM. This missing typology should be reconsidered in the comparative evaluation of these two strategies.